Male homosexuals : their problems and adaptations. - Weinberg, Martin S.; Williams, Colin J. (New York London : Oxford University Press, 1974)
Fonds Suzan Daniel (FSD)
Fonds Suzan Daniel (FSD)F/97/008
Engels
Monografie